LSE Channel Estimation and Performance Analysis of OFDM Systems - Kamışlıoğlu, Bircan; Akbal, Ayhan (Fırat University, 2017)
Orthogonal frequency division multiplex (OFDM) is one of the best approaches to overcome frequency selectivity of channels. In multiple-input multiple-output (MIMO) orthogonal frequency division multiplexing (OFDM) systems, we purposed channel estimation with least squares (LS) estimation method in this paper. To improve channel estimation achievement a LS algorithm is developed, so we obtain Bit Error Rate (BER) performance of channel. Mean Square Error (MSE) of LS estimation calculated and depicted with figures. Signal to noise ratio (SNR) indicated notable efficacy in this paper that obtained by using the LS algorithm, in particular channels with variation in time.
Keywords: Engineering; Mühendislik